Mickiewicz - poeta w wierszach Józefa Ignacego Kraszewskiego = Mickiewicz - the poet in Józef Ignacy Kraszewski?s poems - Woźniak, Jesica (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
This article recalls the value of poetry by Józef Ignacy Kraszewski, who is contemporarily analyzed mainly as a novelist. The author's assumption is to present the dominant features of Kraszewski's lyric, assuming that it is typical for the period of early Romanticism. The reference point is works of Polish romanticism precursor - Adam Mickiewicz. The study matches texts written by the representatives of the first and the second generation of Polish romantics, showing both common elements of poetic output and the significance of the Mickiewicz's works in poetic achievements of one of the most remarkable novelist of the XIX century.
Keywords: Mickiewicz, Adam (1798-1855); Kraszewski, Józef Ignacy (1812-1887); poeta; 19 w.; poet